The leader has a big head - Parker, Jeff; Garcia, Manuel (Edina, Minn. : Spotlight, 2008)
"Join the Hulk, Spider-Man, Captain America, and the rest of the Avengers in these action-packed crime-fighting adventures for all ages"--P. [4] of cover.
"Marvel age"--Cover.
Revision of issue 2 of Marvel adventures, the Avengers.
7 - 11 years
Keywords: Graphic novels; Comic books, strips, etc; Avengers (Fictitious characters); Cartoons and comics; Graphic novels